PEMERIKSAAN INSPEKSI VISUAL ASAM ASETAT UNTUK DETEKSI KANKER SERVIKS - Novi Anggraeni; Dian Eka Januriwasti (STIKES NGUDIA HUSADA MADURA, 2020)
The IVA examination is a screening examination of the pap smear because it is usually cheap, practical, very easy to implement and the equipment is simple and can and can be carried out in addition to a gynecologist. The WHO consultation report states that IVA can detect pre-cancerous lesions with a sensitivity of 66-69% and a specificity of 64-98%. Meanwhile, the positive predictive value and negative predictive value were between 10-20% AND 92-97%, respectively. The method used in this activity is to provide counseling to WUS residents of Kokop village who work together with the local Puskesmas. Prior to this activity, permission was obtained from the Puskesmas. In addition to counseling, the activity was carried out in collaboration with the IVA examination by the Kokop village health center. Participants in this activity were attended by WUS in Kokop village with activities carried out, namely counseling on IVA examinations. During the activity, the mother was very enthusiastic about the material presented.